Swab cloths as a tool for revealing environmental contamination by Q fever in ruminant farms. Issue 3 (6th March 2019) - Carrié, Pauline; Barry, Séverine; Rousset, Elodie; de Crémoux, Renée; Sala, Carole; Calavas, Didier; Perrin, Jean‐Baptiste; Bronner, Anne; Gasqui, Patrick; Gilot‐Fromont, Emmanuelle; Becker, Claire A. M.; Gache, Kristel; et al.
Summary: Q fever is a zoonotic abortive disease of ruminants mostly transmitted by inhalation of aerosols contaminated by Coxiella burnetii . Clusters of cases or even epidemics regularly occur in humans but, to date, there is no consensus about the best way to carry out outbreak investigations in order to identify potential farms at risk. Although environmental samples might be useful during such investigations, there are few baseline data on the presence of C. burnetii in the environment of ruminant farms. We thus investigated dust samples from cattle, sheep and goat farm buildings in order to (a) estimate C. burnetii detection frequency and bacterial loads in the environment, and (b) determine whether this environmental contamination is associated with series of abortions attributed to Q fever. We considered 113 herds with a recent abortive episode potentially related ( n = 60) or not ( n = 53) to C. burnetii . Dust was sampled using a swab cloth and tested by a quantitative PCR method targeting the IS 1111 gene. Coxiella burnetii DNA was detected on 9 of 50 cattle farms, 13 of 19 goat farms and 30 of 40 sheep farms. On 16 cloths, bacterial loads were higher than 10 8 genome equivalents, levels as high as in infectious materials such as placentas and aborted foetuses. Overall, the probability of detecting C. burnetii DNA was higher on small ruminant farms than cattle farms, in herds suspected of Q fever and in large herds. We conclude that swab cloths are a putative indicator of contamination of ruminant farms by C. burnetii .